The synergistic effect of pumice and silica fume on the durability and mechanical characteristics of eco-friendly concrete. (20th June 2018) - Madani, Hesam; Norouzifar, Mohammad Naser; Rostami, Jamshid
Highlights: The synergistic effect of silica fume and pumice on the concrete properties. Eco-friendly cement mixtures with high volume of pumice and silica fume. Recommending at least 3% silica fume in the pumice incorporated mixtures. A significant reduction in GWP using high volumes of pumice and silica fume. Abstract: This study aims at investigating the properties of eco-friendly concretes with high-volume of pumice and silica fume. To reach this purpose, the mechanical and durability characteristics of twenty concrete mixtures were investigated from 3 days to 365 days. In contrast to the previous studies, pumice was utilized at high replacement levels up to 60% in conjunction with silica fume. The durability tests and microstructural investigation indicate that pumice did not improve the chloride resistance and capillary water absorption at 28 days, while due to the synergistic effect of silica fume and pumice, a high level of enhancement on the diffusivity was evident at this age. In 90 days, a significant improvement on concrete durability was observed for the mixtures with pumice, which this enhancement was considerably promoted owing to the use of silica fume. The analyses show that combined use of silica fume and high volume of pumice could provide highly environmentally-friendly concrete. For instance, the mixture with 60% pumice and 9% silica fume (124 kg/m 3 cement) had a 365 days compressive strength of 75 MPa with low level of global warming potential (GWP). In conclusion, the obtained results reveal that use of silica fume as a complementary to pumice is a sustainable solution to produce durable concretes with appropriate characteristics at both early and later ages, especially for those with high volume of pumice. In this regard, utilizing at least 3% silica fume is recommended to provide excellent performance in enhancing the durability and mechanical characteristics.